Desarrollo de un software interactivo de apoyo en los procesos de enseñanza – aprendizaje de la materia de matemática dirigido a los niños de la comunidad evangélica Iñaquito Ievi que cursan el sexto año de educación básica - Bastidas Caizapanta, Carlos Efrén (2015)
This research work was focused on analysis, comparison and discussion of teaching methodology used by the traditionalist school versus new school. Use of TICS and the influence on students using interactive educational software focused on the area of mathematics, the population of these research are teachers and students from the sixth year of basic General education of the Evangelical Church community of Iñaquito. The used models to get information were nonexperimental, participative research methods, descriptive, deductive and the observation technique as well as the mentioned models allowed in this research to gather information and subsequently processed and quantified it, in order to get a criterion for improving the teaching - learning process the obtained results were not far away from the advances in the current educational field and they will serve for implementing and improving teaching methodologies in the institution and the most important fact to benefit the student community.